Accusation and trial argumentation in the cases of former LSSR MGB agents strikers - Gailius, Bernardas (Genocidas ir rezistencija, 2004)
The purpose of this presentation is to discuss the main legal aspects of standard of proof and evaluation of partisan warfare, highlighting issues that could be further explored during the discussion based on the case in which the defendants allegedly belonged to a ‘special taskforce’ of the 2–N Board of the LSSR’s MGB, as well as allegedly were involved in operation aimed at building a legend of the headquarters of the north–eastern Lithuania region.